Ferromagnetic frozen structures from the dipolar hard spheres fluid at moderate and small volume fractions - Russier, Vincent; Malherbe, Jean G.; Alonso-Pereda, Juan José (IOP Publishing, 2023)
We study the magnetic phase diagram of an ensemble of dipolar hard spheres (DHS) with or without uniaxial anisotropy and frozen in position on a disordered structure by tempered Monte Carlo simulations. The crucial point is to consider an anisotropic structure, obtained from the liquid state of the dipolar hard spheres fluid, frozen in its polarized state at low temperature. The freezing inverse temperature βf determines the degree of anisotropy of the structure which is quantified through a structural nematic order parameter, λs. The case of the non zero uniaxial anisotropy is considered only in its infinitely strong strength limit where the system transforms in a dipolar Ising model (DIM). The important finding of this work is that both the DHS and the DIM with a frozen structure build in this way present a ferromagnetic phase at volume fractions below the threshold value where the corresponding isotropic DHS systems exhibit a spin glass phase at low temperature.
Keywords: Dipolos magnéticos; phase diagrams; dipolar interactions; classical spin-glass; magnetic nanoparticles; Monte Carlo simulations